2010
DOI: 10.1038/ng.689
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies a psoriasis susceptibility locus at TRAF3IP2

Abstract: Psoriasis is a multifactorial skin disease characterized by epidermal hyperproliferation and chronic inflammation, the most common form of which is psoriasis vulgaris (PsV). We present a genome-wide association analysis of 2,339,118 SNPs in 472 psoriasis patients and 1,146 controls from Germany, with follow-up of the 147 most significant SNPs in 2,746 PsV cases and 4,140 controls from three independent replication panels. We identified an association at TRAF3IP2 on 6q21 and genotyped two SNPs at this locus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
281
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(294 citation statements)
references
References 38 publications
2
281
1
10
Order By: Relevance
“…Although none of these SNPs have been associated with RA in other studies, rs2522056 has been associated with Crohn's disease (42), an increase in acute phase response (43) and fibrinogen levels and, therefore, can be considered a risk factor for cardiovascular disease (44). The TRAF3IP2 gene has been associated with the risk of developing psoriasis (45) and psoriatic arthritis (46); ICOS, with alopecia areata; KIAA1542, with the presence of anti-dsDNA antibody postivity in systemic lupus erythematosus (47), with the function of the intergenic region between KIAA1919 and REV3L being unknown.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 96%
“…Although none of these SNPs have been associated with RA in other studies, rs2522056 has been associated with Crohn's disease (42), an increase in acute phase response (43) and fibrinogen levels and, therefore, can be considered a risk factor for cardiovascular disease (44). The TRAF3IP2 gene has been associated with the risk of developing psoriasis (45) and psoriatic arthritis (46); ICOS, with alopecia areata; KIAA1542, with the presence of anti-dsDNA antibody postivity in systemic lupus erythematosus (47), with the function of the intergenic region between KIAA1919 and REV3L being unknown.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 96%
“…Advances in high-throughput genotyping technologies and the completion of the genomewide database of common genetic sequence variation (HapMap project) have paved the way to the identification of a number of psoriasis susceptibility genes by means of GWAS (Capon et al 2008;de Cid et al 2009;Nair et al 2009;Zhang et al 2009;Ellinghaus et al 2010;Huffmeier et al 2010;Strange et al 2010;Stuart et al 2010) and subsequent meta-analysis (Ellinghaus et al 2012a;Tsoi et al 2012). Collectively, these studies identified 36 independent psoriasis-associated regions within individuals of European ancestry (Tsoi et al 2012), plus five more uniquely associated in the Chinese population (Sun et al 2010).…”
Section: Psoriasis Susceptibility Genes Identified By Gwassmentioning
confidence: 99%
“…19,96,97 Similar to IBD, GWAS data from psoriasis specimens show that IL-23R and Act1 are psoriasis-associated genes. [98][99][100] In mice, intracutaneous injection of IL-23 causes psoriasis-like epidermal hyperplasia; this skin inflammation is ameliorated in Il17a-, Il17ra-or Il22-deficient mice. 101,102 The TLR7/8 agonist imiquimod (IMQ) can also induce and exacerbate a psoriasis-like syndrome in mice.…”
Section: Il-17dmentioning
confidence: 99%